Prevalence of foodborne parasitic infections in market-sold aquatic products and high-risk populations in Shanghai, China: surveillance between 2022 and 2024 - Simin Dai; Jun Feng; Min Chen; Huanyu Wu; Yujuan Shen; Qing Yu; Jian Chen (BMC Infectious Diseases)
Abstract Background Substantial achievements have been made in preventing and treating human parasitic diseases in China over the past six decades. However, with the recent progression of economic globalization and food diversification, foodborne parasitic diseases have become a significant public health challenge. Here, we investigated and analyzed the characteristics of foodborne parasitic infections arising from market-sold aquatic food products and in key populations. Methods Freshwater, seawater, and pickled products were randomly obtained from agricultural trade markets, restaurants, supermarkets, and retail stores in four districts of Shanghai from 2022 to 2024. Parasite metacercariae or larvae were subsequently detected in these aquatic products via artificial digestion or dissection methods. Fecal samples from 698 diarrhea outpatients from the intestinal clinics of hospitals were analyzed via molecular methods. Results Of the 1,914 aquatic samples, 163 (8.52%) tested positive for parasites. Nine out of 1,086 freshwater products tested positive for parasites, including Clonorchis sinensis (7; 0.64%) and Gnathosotoma spinigerum (2; 0.18%). Anisakis was detected only in 7 of 27 seawater fish species, with contamination rates ranging from 6.00 to 100.00%. Echinostoma metacercariae was found only in marinated mud snails (20.43%). The prevalence of Clonorchis sinensis metacercariae in freshwater fish was highest in the second quarter (April–June), and catering samples presented the highest contamination rate, at 12.96%. In the sequence analysis, only one outpatient sample tested positive for parasitic infection, identified as Cryptosporidium meleagridis. No Giardia lamblia was found in the participants. Conclusions Foodborne parasite contamination occurs in market-sold aquatic food products in Shanghai Municipality, although the incidence of parasite infection was low in the key populations tested. Further studies are needed to establish more comprehensive information that could improve public health and human food safety awareness.